Sustainable Production and Physicochemical Evaluation of Soap from Locally Sourced Materials: A Comparative Study with Commercial Products - Adam, Sulaiman Umar; Sufyan, Mansur Bala; Ahmad, Muhammad Musa (FUDMA Journal of Sciences, 2026)
This study investigated the sustainable production and comprehensive physicochemical evaluation of soap using locally available raw materials in Daura, Katsina State, Nigeria. Seven formulations were developed from blends of palm kernel oil (PKO), groundnut oil (GO), cow fat (CF), and used cooking oil (UCO), using alkali extracted from plantain (Musa paradisiaca) peel ash as a renewable substitute for commercial sodium hydroxide. Saponification was conducted by the semi-boiled method at 60–75 °C. Oil characterization by AOAC-validated methods yielded saponification values of 248.5 ± 2.3, 195.4 ± 2.8, 196.8 ± 2.5, and 189.4 ± 3.2 mg KOH/g for PKO, GO, CF, and UCO, respectively. Plantain peel ash extract provided a KOH-equivalent concentration of 1.85 ± 0.08 mol/L at pH 12.8 ± 0.3. The optimized formulation (Blend B: 65% PKO, 20% GO, 10% CF, 5% UCO) produced potassium soap with a total fatty matter (TFM) content of 76.8 ± 1.1%, pH 10.0 ± 0.2, hardness score 8.5 ± 0.3/10, foam stability 68.5 ± 2.8% at 5 min, and cleaning efficiency 78.1 ± 1.6%. Comparative analysis against seven commercial sodium soap brands under identical analytical conditions confirmed comparable or superior quality for the optimized blend. The ash-based process reduced per-kilogram production costs by 13.7% relative to conventional NaOH-based manufacture (₦1,450 vs. ₦1,680/kg). Valorization of plantain peel waste and used cooking oil addresses dual environmental challenges, supporting circular economy principles and scalable small-enterprise production in rural settings